2011
DOI: 10.1108/13552541111113907
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing in South Africa: building on the foundations

Abstract: Type of Paper General Review PurposeIn a previous Rapid Prototyping Journal paper, the authors reviewed the first decade of Rapid Prototyping (RP) use within the Republic of South Africa (RSA). The paper analysed its strengths, weaknesses, opportunities and threats, and proposed a "road-map" for future development. Much has happened in the intervening years since that article was published and this paper seeks to update readers on the current situation in RSA. In particular, it reports the extensive developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…The history and growth of the technology was described by De Beer [4] and Campbell, De Beer and Pei [5]. Figure 1 shows the acceleration in the acquisition of AM systems in South Africa since 2010, after the first years of slow growth.…”
Section: Additive Manufacturing In South Africamentioning
confidence: 99%
“…The history and growth of the technology was described by De Beer [4] and Campbell, De Beer and Pei [5]. Figure 1 shows the acceleration in the acquisition of AM systems in South Africa since 2010, after the first years of slow growth.…”
Section: Additive Manufacturing In South Africamentioning
confidence: 99%
“…Existing literature suggested that the technology was being applied but only at an experimental level but the studies themselves offered little insight into the factors preventing the use of AM as a means of transforming the manufacturing sector (Campbell and De Beer and Pei, 2011). In this study the following research questions were explored in order to provide this insight:…”
Section: Methodsmentioning
confidence: 99%
“…AM technology has also been used to fabricate architectural models [12,7]. Campbell et al [4] have reviewed the use of AM technology for terrain modelling, architectural modelling, and other applications in South Africa.…”
Section: Introductionmentioning
confidence: 99%